The Role of Lipoxidation in the Pathogenesis of Diabetic Retinopathy - Augustine, Josy; Troendle, Evan P.; Barabas, Peter; McAleese, Corey A.; Friedel, Thomas; Stitt, Alan W.; Curtis, Tim M. (Frontiers in Endocrinology, 2021)
Lipids can undergo modification as a result of interaction with reactive oxygen species (ROS). For example, lipid peroxidation results in the production of a wide variety of highly reactive aldehyde species which can drive a range of disease-relevant responses in cells and tissues. Such lipid aldehydes react with nucleophilic groups on macromolecules including phospholipids, nucleic acids, and proteins which, in turn, leads to the formation of reversible or irreversible adducts known as advanced lipoxidation end products (ALEs). In the setting of diabetes, lipid peroxidation and ALE formation has been implicated in the pathogenesis of macro- and microvascular complications. As the most common diabetic complication, retinopathy is one of the leading causes of vision loss and blindness worldwide. Herein, we discuss diabetic retinopathy (DR) as a disease entity and review the current knowledge and experimental data supporting a role for lipid peroxidation and ALE formation in the onset and development of this condition. Potential therapeutic approaches to prevent lipid peroxidation and lipoxidation reactions in the diabetic retina are also considered, including the use of antioxidants, lipid aldehyde scavenging agents and pharmacological and gene therapy approaches for boosting endogenous aldehyde detoxification systems. It is concluded that further research in this area could lead to new strategies to halt the progression of DR before irreversible retinal damage and sight-threatening complications occur.